(untitled) (Journal of the College of Basic Education, 2022)
If any good deed or thought, whether divine or human, is considered as a biography or remembrance immortalized by people benefiting from it, or by their belief in its virtue in changing aspects of their lives, then the philosophers of history have seen some of them that history is nothing but the biography of the great men, although the writers said It is a literary art in which the writer or the author narrates the life of a historical personality or a group of people who were characterized by satisfactory features for everyone, and they called it the (historical biography), but if he wants to talk about himself, they call it (the biography), and each of these two types has goals that I am not going to say about. ) Although the second type depends on the one who writes or writes of his own free will or commission,